2006
DOI: 10.1080/01902140600959630
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Kinase C Epsilon Causes Ciliated Bovine Bronchial Cell Detachment

Abstract: This study defines the in vitro phenomenon of ciliated bovine bronchial epithelial cell (BBEC) detachment from the basal epithelium and regulation of cilia motility mediated through protein kinase C epsilon (PKCε). The authors determined the time course of activation and downregulation of PKCε by the known PKC activator phorbol 12-myristate 13-acetate (PMA) and demonstrate that chemical inhibition of PKC by calphostin C or the novel PKC isoform inhibitor Ro 31-8220 induced striking detachment of ciliated BBECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…In our localization studies of RACK1 in airway epithelial cells, we anticipated that a targeting protein for PKC might be localized to the apical region of both ciliated cells and basal airway cells, because PKCe is an important regulator of cilia motility and ciliated cell attachment (Slager et al 2006). Contrary to this hypothesis, our IHC results showed that RACK1 is localized exclusively on non-ciliated basal mammalian airway cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our localization studies of RACK1 in airway epithelial cells, we anticipated that a targeting protein for PKC might be localized to the apical region of both ciliated cells and basal airway cells, because PKCe is an important regulator of cilia motility and ciliated cell attachment (Slager et al 2006). Contrary to this hypothesis, our IHC results showed that RACK1 is localized exclusively on non-ciliated basal mammalian airway cells.…”
Section: Resultsmentioning
confidence: 99%
“…In the latter phenomenon, inhibition of PKCe by a novel PKC inhibitor, Ro 31-8220, mimics the effects seen in viral infections or cigarette smoke exposure (Sisson et al 1994), producing widespread detachment of ciliated cells and cilia loss (Slager et al 2006). We were interested in determining how this mechanism of ciliated cell detachment is regulated and hypothesized that RACK1 would be localized to the cilia or apical region of ciliated cells as a Figure 4 RACK1 is not localized to human airway goblet cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to CBF, SAVA was used to determine the number of motile cilia as previously described (23). Briefly, the number of motile points from each digital video image was determined using a software algorithm in SAVA.…”
Section: Methodsmentioning
confidence: 99%